Pengaruh Kualitas Pelayanan, Inovasi Pelayanan, Kualitas Produk, Kepuasan Pelanggan dan Loyalitas Pelanggan Sepeda Motor Honda - I Ketut Ardika; I Nengah Dasi Astawa (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTEra of globalization and the competitive environment and competition , the focus for the business world is a point for every company . To face the stiff competition , the quality of products and services produced is very important in order to enhance the growth of a company . These conditions demand a high quality of human resources to manage the various problems that exist . Low overhead business strategy is inseparable scope of the management company relating to keekfektifan and keefesienan production both for users of raw materials and production system as well as from the use and management of human resources.Amid the current automotive business competition , Honda also must perform service quality , service innovation and product quality . Important to be able to attract customers . The management of Honda always establish or maintain a good relationship to customers , it was all done in order to strengthen the relationship between pihat Honda with customers' in order to increase customer loyalty. The technique of collecting data using questionnaires , data analysis is a statistical method used Structural Equation Model (SEM). then data will be processed with SPSS and AMOS facilities . SPSS is used to imput data obtained from the results of the research data collection , whereas AMOS are used to display the results of research on the relationship between the variables.